Emerging infectious disease selects for darker plumage coloration in greenfinches - Männiste, Marju; Hõrak, Peeter (Frontiers in Ecology and Evolution, 2014)
Outbreaks of emerging infectious disease offer a unique chance to study viability selection in action in short time windows. Finch trichomonosis, caused by a protozoan Trichomonas gallinae emerged in Great Britain in 2005 and led to epidemic mortality and a significant population decline of greenfinches, Carduelis chloris in UK and Northern European countries in subsequent years. We recorded covariation between plumage characteristics and trichomonosis-induced mortality among wild-caught greenfinches brought into captivity in Tartu, Estonia. Occurrence of fault bars (markers of stressful conditions experienced during feather growth) on tail feathers was five times higher among the dead birds than among survivors. Black (eumelanotic) compartments of tail feathers of survivors were on average 22 % darker than feathers of dead birds. Such pattern is best explained by proposed pleiotropic effects of genes involved in eumelanin production on immune function. These findings suggest that melanin-based coloration can evolve via mechanisms that are independent of visual information provided by the pigment.